Antibiotic-Resistant-Bacterial Infection of Diabetes Mellitus-Induced Ulcers: A Narrative Review on a Healing Ointment - Jaka Aryantara Kuntala; Mutmainnah Agustiawan Umar; Qurrotu Ayni; Dimas Andrianto (IPB University, 2020)
Gangrene is the main reason why diabetes mellitus patient’s leg amputation should be done. Natural compounds which are contained in coffee grounds extract can actually act as antibacterial substances by inhibiting the growth of Methicillin-Resistant Staphylococcus aureus (MRSA) that resistant to several antibiotics. Coffee grounds become waste caused by people are underusing this material and the high production level of coffee grounds in Indonesia. The purpose of this study was to examine the content of antimicrobial compounds from coffee grounds that can heal wounds caused by diabetes mellitus and to create a formulation of coffee ground based ointment for diabetes mellitus wound healing. Methods used in this research are narrative review from literatures, normality test, and T-test. The conclusion of this narrative review, natural compounds such a trigonelline, caffeine, and chlorogenic acid found in coffee grounds are capable of MRSA growth inhibition at concentration 44%. Coffee grounds based ointment with 1% (w/w) of ointment preparation is expected to reduce coffee grounds waste by developing new product as diabetes mellitus wound healer.